An app to keep: smartphone-based dispatch of community first responder to cardiac arrest - Tore Marks; Bibiana Metelmann; Peter Brinkrolf; Karl Christian Thies; Klaus Hahnenkamp; Camilla Metelmann (BMC Cardiovascular Disorders)
Abstract Background Smartphone-based alerting of community first responders to out-of-hospital cardiac arrest (OHCA) is associated with enhanced survival. Community first responders are volunteers, who are dispatched by the emergency dispatch centre, if they are in close proximity to an OHCA to decrease time until first chest compression. For a community first responder system to be successful, it is essential to recruit and retain as many qualified community first responders as possible. This study evaluates the appraisal and retention rate of an app-based community first responders system over a period of 3 years. Methods A longitudinal study among community first responder in a rural northern Germany was conducted using an online-survey. A questionnaire (7 open questions, 22 single choice questions and 2 multiple choice questions) was distributed to all community first responders (FR) via e-mail in October 2018, 2019 and November 2020. Ethical approval was obtained, informed consent was given by all participants. Results The response rate was 69%, 43% and 38% in the first, second and third year, respectively. Three years after implementing the system 96% of the users stated they still had the app installed. After the first year, 21% of participants observed improvements. In the second year, this number was 15%, and 31% in the third year. The opinion regarding the medical benefit of the app was stable. Nine out of ten participants would recommend the app to others. Of all participants 70% identified as male and 66% were 35 years old or younger. Main barrier to using the app was excessive „battery consumption“. Conclusions The community first responder system attracts a predominantly young and male user base. The retention rate of 96% over the three years observation period is high. The main barrier to app usage is excessive battery consumption. The users’ positive perceptions regarding the app’s medical advantages and the favorable perception of its functionality have resulted in a steadfast high recommendation rate.